Dwell Fatigue Crack Growth Behavior of CP-Ti TA2 Welded Joint at 25 °C and 200 °C - Le Chang; Lei Lu; Binbin Zhou; Changyu Zhou (Metals, 2023)
We report on studies of the dwell fatigue crack growth (FCG) behavior of commercial pure titanium (CP-Ti) TA2 weld joints at 25 °C and 200 °C. Taking into account the effects of load ratio and dwell temperature, the impact of dwell on FCG behavior and the associated fracture mechanism are clearly demonstrated. Meanwhile, in order to illustrate creep–fatigue interaction, finite element simulations are also performed to analyze the evolution of stress and strain field near the crack tip. The results show that with the increase in dwell temperature, the FCG rate is increased. Furthermore, the effect of dwell on FCG behavior is more pronounced at higher load ratios. Finite element simulation results indicate that dwell induces creep stress relaxation and leads to an increase in the equivalent plastic strain near the crack tip. With the increase of dwell temperature and load ratio, the more pronounced creep deformation may lead to a creep-dominated FCG behavior. As consistent with the above analysis, the examination of the fracture surface reveals that more cavities and secondary cracks may be observed because of the increased creep deformation at the higher dwell temperature and load ratio.